Bioética e nanotecnologia: a moralidade como princípio orientador na busca pela formulação de marcos regulatórios aos nanocosméticos - Tose, Laura Pimenta Krause (2017)
The cosmetics industry plays an increasingly significant role in the global economy. Among the technological advances promoted by this segment, we find the manufacture of nanocosmetics. The absence of regulatory milestones and the way in which these products are introduced into the market and perceived by consumers, with regard to their possible health and benefits risks, is what we intend to analyze. The lack of specific legislation constitutes a factor of aggravation of the problem, which indicates, in the sense of the necessity of studies directed to the analysis of the social, ethical and legal impacts of this technological incorporation. The investigation pointed to the need for the applicator of the right to consider infringement of the fundamental rights involved, being based in this case on bioethical principles as well as on the rights to life, information and health of consumers, considering that they should prevail over private interests related to the profitability and competitiveness of the business. In order to safeguard the guarantee of a dignified life for consumers, it is proposed to apply the ethical principles involved, and especially morality, as guiding principles in the search for the formulation of regulatory frameworks for nanocosmetics, considering the uncertainty of risks to that are submitted.